Development of degraded ravine lands of Western India using Sapota (Achras zapota) plantation with terracing vs. trenching‐on‐slope‐based conservation measures. (3rd August 2020) - Kumar, Raj; Bhardwaj, Ajay Kumar; Rao, Battu Krishna; Vishwakarma, Anand Kumar; Bhatnagar, Pratap Ray; Patra, Sridhar; Kumar, Gopal; Kakade, Vijaysinha; Dinesh, Dhakshanamoorthy; Pande, Vinod Chandra; Singh, Gaurav; Dobhal, Sneha; et al.
Abstract: Globally, ravine landscapes are considered among the world's most degraded ecosystems. Restoring ravines is considered a high priority item in the conservation programmes, and tree establishment augmented with appropriate soil and water conservation measures is the most sought‐after restoration strategy. This study examined the impact of terracing and trenching on runoff, soil loss, and soil properties along with Sapota ( Achras zapota ) growth, fruit yield, biomass and carbon stock during 6 years (2010–2015) in a degraded ravine land of Western India. The four soil and water conservation strategies tested were (1) bench terracing + Sapota (Bt), (2) bench terracing + Sapota with crop cultivation (BtCr), (3) continuous slope + Sapota (Sl), and (4) continuous slope + Sapota with trenches (SlTr). All conservation techniques increased Sapota height (Bt: 54%; BtCr: 27%; SlTr: 35%) and basal diameter (Bt: 36%; BtCr: 18%; StCr: 22%) compared to Sl. Biomass and carbon stock of Sapota were in the order of Bt > SlTr > BtCr > Sl. During the droughtperiod, fruit yield was highest in Bt followed by BtCr, SlTr, and least in Sl. The treatment SlTr and Bt reduced runoff by 16–34% and soil loss by 15–25%, compared to Sl. The growth and biomass were strongly correlated with soil loss. The findings suggested that bench terracing is the best soil and water conservation measure for restoring highly degraded ravines of Western India. Under circumstances where terracing is not feasible, trenching could be a significant step along with Sapota plantation to restore these ravines.